Successful treatment of refractory Gastric Antral Vascular Ectasia (GAVE) in a cirrhotic patient with transcatheter arterial embolisation in a tertiary care facility in Pakistan: a case report - Alam, Laima; Ayesha Usmani (Journal of the Pakistan Medical Association, 2021)
Gastric antral vascular ectasia (GAVE) is a rare but important cause of upper gastrointestinal bleeding that may present with refractory anaemia or overt gastrointestinal bleeding requiring multiple admissions and resuscitation. Although endoscopic therapies are considered first line treatment for the management of refractory gastric antral vascular ectasia, angiographic embolisation of the culprit vessel(s) may emerge as an effective and safe treatment modality in the near future. Here, we present the case of a middle-aged gentleman with refractory gastric antral vascular ectasia, who was not responding to repeated sessions of Argon Plasma Coagulation (APC) and was successfully treated with trans-catheter arterial embolisation of gastro-duodenal artery. Keywords: Gastric antral vascular ectasia, Bleeding, Watermelon stomach, Argon plasma coagulation, Continuous...